2005
DOI: 10.1037/0022-0167.52.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon Changes: An Exploration of Racial Identity Themes of Multiracial People.

Abstract: The current study explored essential themes of racial identity development among 10 self-identified multiracial adults from a variety of racial backgrounds. Participants were interviewed using a semistructured protocol, and the interviews were recorded, transcribed, and then coded for themes by research team members. Four primary themes were identified: encounters with racism, reference group orientation, the "chameleon" experience, and the importance of social context in identity development. A number of subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(168 citation statements)
references
References 13 publications
6
161
1
Order By: Relevance
“…The messages that parents give to their children may influence mixed race individuals' identification with one race over the other, with their minority or dominant race parent (Gillem et al, 2001;Miville et al, 2005), an integrated identity (Kerwin et al, 1993;Miville et al, 2005), or may even create confusion in developing a racial identity (Gillem et al, 2001). Some research has suggested that parents are often aware that even if they encourage a biracial/multiracial identity for their children, there would be many instances in which a child may be asked to choose one race (Gillem et al, 2001;Kerwin et al, 1993).…”
Section: Factors Influencing Mixed Race Identity Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The messages that parents give to their children may influence mixed race individuals' identification with one race over the other, with their minority or dominant race parent (Gillem et al, 2001;Miville et al, 2005), an integrated identity (Kerwin et al, 1993;Miville et al, 2005), or may even create confusion in developing a racial identity (Gillem et al, 2001). Some research has suggested that parents are often aware that even if they encourage a biracial/multiracial identity for their children, there would be many instances in which a child may be asked to choose one race (Gillem et al, 2001;Kerwin et al, 1993).…”
Section: Factors Influencing Mixed Race Identity Developmentmentioning
confidence: 99%
“…Consequently, in accordance with the U.S. laws of hypodescent which formed the basis of the one drop rule, an individual who had any Black blood in their heritage would be categorized as Black, even if they had no discernible Black features (Brown, 1995;Daniel, 1992;Gillem, Cohn, & Throne, 2001;Kerwin et al, 1993;McClain DaCosta, 2004;Miville et al 2005;Root, 1998;Spickard, 1992;Suzuki-Crumly & Hyers, 2004).…”
Section: Scientific Discourse On Racial Mixturementioning
confidence: 99%
See 3 more Smart Citations